Integrative Model for Building Good Listening Skills in Islamic-Based Early Childhood Education - Malihah, Zahro; Jamil, Wafa Hamidatul (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2025)
Early childhood is a crucial stage for shaping foundational character, including listening habits that influence social, emotional, and communication development. In Islamic-based educational settings, listening is viewed not only as a cognitive skill but also as an ethical value rooted in religious teachings, making its cultivation both pedagogical and spiritual. This study aims to develop an integrative model for forming good listener character in early childhood at an Islamic-based kindergarten in Bogor City. Using a qualitative case study, the research found this character formation is not spontaneous, but the outcome of planned, gentle, and meaningful habituation. The “Pillar of Morality” program effectively instilled active listening through songs, games, storytelling, and prayer. This process aligns with Lickona’s three domains including moral knowing, moral feeling, and moral acting—but was expanded in the Islamic context with a fourth domain: spiritual meaning. Thematic analysis produced an integrative model consisting of four character domains (cognitive, affective, behavioral, and spiritual) supported by three main factors: teacher exemplification, routine habituation, and a spiritually enriched environment. This model highlights that character education must operate holistically by integrating role modeling, consistent practice, and spiritual context. The study contributes theoretically to Islamic-based character education and offers practical guidance for fostering a culture of active listening grounded in manners and affection.